THE EFFECT OF CHARGING CONDITION FOR CONDUCTED EMISSION VALUE OF INFORMATION TECHNOLOGY EQUIPMENT - Agung Yanuar Wirapraja; Ika Prawesty Wulandari (Pusbindiklat - LIPI, 2018)
Currently, IT devices, especially mobile phone and notebook, have become a staple for humans. These devices can’t be separated from human activities. Mobile phone or notebook using those are too often can lead people to conduct any charging process when that device is being used. In general, there are three conditions for any devices when the charging process is being performed, such as: off, standby, and normal use (music on). This research objective is to compare the result on conducted emis- sion testing when mobile phone and notebook at the plugging charge for the conditions: off, stand by, and normal use (music on). Testing method refers to CISPR 22 Standards at Clause Mains Terminal Disturbance Voltage. Testing result for mobile phone and notebook show that all of testing sample perform conducted emission value with quasi peak value meet the requirement of CISPR 22. The amount of 80% testing sample, perform the highest quasipeak margin value when the off condition of devices.